Creating knowledge maps using Memory Island - Yang, Bin; Ganascia, Jean-Gabriel (International Journal on Digital Libraries, 2017)
Knowledge maps are useful tools, now beginning to be widely applied to the management and sharing of large-scale hierarchical knowledge. In this paper, we discuss how knowledge maps can be generated using Memory Island. Memory Island is our cartographic visualization technique, which was inspired by the ancient “Art of Memory”. It consists of automatically creating the spatial cartographic representation of a given hierarchical knowledge (e.g., ontology). With the help of its interactive functions, users can navigate through an artificial landscape, to learn and retrieve information from the knowledge. We also present some preliminary results of representing different hierarchical knowledge to show how the knowledge maps created by our technique work.